Kolja as a Symptom. Ideology, Phantasm and Nation in Jan Svěrák's Film - Tippner, Anja (Iluminace, 2001)
An analysis of Jan Svěrák's bitter comedy Kolya and its study from the psychoanalytic point of view of film ideology, the depiction of society and nation. Symptomatics of the film, motifs and symbols.
Keywords: Kolja 1996; film aesthetics; symbol in film; psychoanalysis and film; politics in film; ideology in film; society in film; motive in film; ethnic groups in film; Czechs in film